1997
DOI: 10.1111/j.1601-0825.1997.tb00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of the oral mucosal lesions seen in association with HIV infection

Abstract: Oral lesions cause considerable morbidity in association with HIV infection. Their successful management depends upon accurate diagnosis and the use of appropriate therapy. Various treatment approaches are described for some of the common oral lesions including Kaposi's sarcoma, oral candidiasis, hairy leukoplakia and recurrent oral ulcers associated with HIV disease. This paper will discuss the therapies available in the USA and UK. In other countries some of the drugs discussed will be available in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
8

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
1
3
0
8
Order By: Relevance
“…Although our study was directed towards OHL, the presence of oral candidiasis and OHL was also verified, simultaneously, as being the two most common oral lesions in HIV‐infected adults. The association between the presence of OHL and oral candidiasis verified in this study has also been observed in many other studies in the US and Europe (2, 3, 5, 38, 39).…”
Section: Discussionsupporting
confidence: 90%
“…Although our study was directed towards OHL, the presence of oral candidiasis and OHL was also verified, simultaneously, as being the two most common oral lesions in HIV‐infected adults. The association between the presence of OHL and oral candidiasis verified in this study has also been observed in many other studies in the US and Europe (2, 3, 5, 38, 39).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, metallic taste might be elicited by oral yeast infections (29), burning mouth syndrome (30), damage by stapedectomy or anesthesia of the chorda tympani (31,32), artificial sweeteners (33), and dental amalgam fillings (34). These factors may have influenced the prevalence of metallic taste in the current study.…”
Section: Discussionmentioning
confidence: 92%
“…They may alter facial appearance, impair speech, and cause difficulty with swallowing, which may lead to significant weight loss. The management of the oral manifestations of HIV infection in North America and Europe has been extensively reviewed (Greenspan and Shirlaw, 1997;Shirlaw et al, 2002). Protocols for the resourcepoor setting are reviewed in Question 4 of this workshop.…”
Section: Diagnosis and Management Of Hivassociated Orofacial Lesionsmentioning
confidence: 99%